Penguatan Kapasitas UMKM melalui Pelatihan Tata Kelola Keuangan dan Pengembangan Rumah Produksi Bersama Sahabat UMKM Pamulang (SUP) - Achmad Rifai; Dian Priastiwi; Syofia Sofatunisa Ramdayani; Sari Sari; Yozar Putra Jaya (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Strengthening the capacity of micro, small, and medium enterprises (MSMEs) is a strategic effort to enhance business competitiveness and sustainability, particularly within the Pamulang MSME Friends (SUP) community. This community service activity aims to improve MSMEs’ financial management capabilities and increase production efficiency through the development of a joint production house. The main challenges faced by partners include limited financial literacy, the absence of systematic financial transaction records, and inadequate production facilities. The implementation of the program was carried out through training activities, mentoring in the use of the APIK financial recording application, and facilitation in designing a collaborative production house model. The results indicate an improvement in MSMEs’ understanding of financial management, including the ability to record transactions systematically, separate business and personal finances, and calculate production costs more accurately. Furthermore, the establishment of a joint production house contributes to greater cost efficiency, increased production capacity, improved product quality, and stronger collaboration among MSME actors. Therefore, this activity contributes to creating a more structured, efficient, and sustainable MSME ecosystem that supports long-term business development.